Evolution of graft morphology and function after recellularization of decellularized rat livers. (26th June 2017) - Butter, Antje; Aliyev, Khalid; Hillebrandt, Karl‐Herbert; Raschzok, Nathanael; Kluge, Martin; Seiffert, Nicolai; Tang, Peter; Napierala, Hendrik; Muhamma, Ashraf I.; Reutzel‐Selke, Anja; Andreou, Andreas; Pratschke, Johann; et al.
Abstract: Decellularization of livers is a well‐established procedure. Data on different reseeding techniques or the functional evolution and reorganization processes of repopulated grafts remains limited. A proprietary, customized bioreactor was established to repopulate decellularized rat livers ( n = 21) with primary rat hepatocytes (150 × 10 6 cells) via the hepatic artery and to subsequently evaluate graft morphology and function during 7 days of ex vivo perfusion. Grafts were analysed at 1 h, 6 h, 12 h, 24 h, 3 days, 5 days and 7 days after recellularization (all n = 3) by immunohistological evaluation, hepatocyte‐related enzyme (aspartate transaminase, alanine transaminase and lactate dehydrogenase) and albumin measurement in the perfusate. This appears to be the first available protocol for repopulation of rat livers via the hepatic artery. Within the first 24 h after repopulation, the hepatocytes seemed to migrate out of the vascular network and form clusters in the parenchymal space around the vessels. Graft function increased for the first 24 h after repopulation with a significantly higher function compared to standard two‐dimensional culture after 24 h. Thereafter, graft function constantly decreased with significantly lower values after 6 days and 7 days of perfusion, although histologically viable hepatocytes were found even after this period. The data suggests that, owing to a constant loss of function, repopulated grafts should potentially be implanted as soon as cell engraftment and graft re‐organization are completed. Copyright © 2016 John Wiley & Sons, Ltd.